Analisis Kepemimpinan Kepala Desa dalam Meningkatkan Produktivitas Kerja Aparatur Pemerintah di Desa Marisa Utara Kecamatan Marisa Kabupaten Pohuwato - Hasman Umuri; Edy Sijaya (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2024)
This research aims to analyze the Village Head's Leadership, as was the initial argument in this research, that village officials and village heads are the lowest basis for community services. The high or low quality of the services provided does not only depend on the performance of village officials as subordinates, but also the leaders. A person's leadership will determine the progress or decline and life or death of the organization they lead. Village governments, like central and regional governments, are required to provide maximum service to the community and be able to respond to the increasingly high demands of the community, both in terms of quality and quantity. Considering the importance of leadership as a determining factor in the success or failure of an organization and business, this research aims to see how the Village Head's leadership efforts are in increasing the productivity of the performance of the apparatus and how the leadership of the Village Head is related to increasing the productivity of the performance of the Village Government Apparatus in North Marisa, Marisa sub-district, Pohuwato district. . With this type of qualitative research, the research informants are the village head and village officials, data collection using documentation techniques, observation and in-depth interviews. The data analysis used consists of data reduction, data presentation, and drawing conclusions. The results of the research show that the Head of North Marisa Village applies several approaches such as a democratic approach, this approach makes it easier for leaders to develop responsibilities such as involving employees in decision making, but not only that, the Head of North Marisa Village also applies other leadership approaches such as laissez leadership. faire (free reign) and charismatic. Then it is strengthened by several factors such as personal factors, team factors and leadership factors, and the most dominant of these three factors is the leadership factor because with the presence of a leader there is someone who provides encouragement, input and guidance to subordinates or officers in their work.